The Implementation Of Green Architecture In Music Center Building - Harisdani, D. D; Tantri, W (Jurnal Koridor, 2019)
Green architecture can be implemented on the design of a music center building in Medan, Indonesia. The effectiveness of the studying process is related to the environment of the study places created through the implementation of green architecture into a natural, comfortable and tranquil environment both in and outside of the building. With this implementation, an energy-efficient building is designed which supports the development of the city’s green area. To design the building itself, the architectural and non –architectural design stages are carried out by analyzing through various libraries and media as a consideration in solving design problems. The design of this building is related to the orientation of the building itself which utilizes natural lightning, attention to the direction of wind to create natural air circulation, provision of parking spaces and open spaces for convenience and the reuse of water resources which is a green architectural concept that is implemented in urban area’s buildings.